Optimal operation of hybrid energy system - Zhao, Yidan (2016)
With the ever increasing demand on energy, how to improve efficiency of non-renewable energy resources and reduce energy consumption has been a challenging question. In household energy consumption field, one of the answers coming up is the application of hybrid power system. This residential energy system typically consists of a fuel cell system with a combined heat and power (CHP) system and a battery. This report deals with a modified system, with absorption chiller replacing thermal load, and demonstrates how the minimum daily operation cost and optimal energy dispatch schedule can be obtained ahead of time. In this project, coding and optimization algorithm are based on MATLAB. With electrical demand data and other parameters given, the program is able to determine a near minimum operation cost and generate the detailed power dispatch schedule for all devices in the system.